Tindak Pidana Penghinaan terhadap Kepala Negara dalam KUHP Baru dan Hukum Pidana Islam - Egifa Andika Lubis; Rajin Sitepu (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The rearrangement of the article regarding insulting the president or vice president is not to silence the people but rather to protect those who often criticize the government in a way that is good for the public interest. However, the re-regulation of this criminal act has sparked debate. On the other hand, the president is also closely linked to the interests and power of the state, so he needs legal norms that regulate his dignity and honor so that he is well maintained. The President and Vice President have the principle of Primus Interpares, or first of equals. The purpose of this writing is to gain an understanding of the background behind the regulation of this article in the New Criminal Code, as well as understanding what differentiates it from the article regarding insulting the president which in the previous legal arrangement in the Criminal Code was declared contrary to the Constitution by the Constitutional Court. Apart from that, this article also aims to understand the potential point of intersection of the substance of the article with the right to freedom of expression/opinion and freedom of the press and finally to understand this problem from the perspective of Islamic Criminal Law. This research method uses normative juridical and comparative juridical. The results of this research show that to examine the issue of the article regarding insulting the Head of State which must be defended because the Head of State has the principle of primus Interpares attached to the Head of State because of their status to serve and run the government of the Republic of Indonesia, in other words they provide service to the people, so the right -Special rights are reasonable to obtain. What differentiates the article on insulting the Head of State in the New Criminal Code from the Criminal Code which was declared contrary to the constitution by the Constitutional Court, namely: Article 217, Article 218 and Article 219 and Article 220, this article uses the offense of complaint, meaning that only the president and vice president have legal standing complained about the alleged criminal act and in accordance with the mandate of the Constitutional Court's decision, the Government has changed the offense of insulting the President and Vice President which was previously a formal offense to a material offense. The article regarding insulting the Head of State does not conflict with the right to freedom of opinion and freedom of the press in criticizing the Head of State in a manner that is good for the public interest. This can still be done even though the article regarding insulting the Head of State is re-regulated in the New Criminal Code. From the perspective of Islamic Criminal Law, based on history, it is an insulting act Based on history, acts of insulting the head of state can be described as insulting acts against the friends of the Prophet Muhammad, namely the Khulafaur'rasyiddin. These actions took the form of criticizing the friends and even slandering the Prophet's friends. Because indeed Allah really hates the act of criticizing or insulting other people. Because that is a despicable thing.